Left on our own: COVID-19, TRIPS-Plus Free Trade Agreements, and the Doha Declaration on TRIPS and Public Health - Melissa Omino; Joanna Kahumbu (South Centre, 2022)
The cusp of the twentieth anniversary of the WTO Doha Declaration on the TRIPS Agreement and Public Health (hereafter "the Declaration") was marked by a global pandemic. The Declaration and its iteration in the Agreement on Trade Related Aspects of Intellectual Property Rights (hereafter "TRIPS") Article 31 bis, should have helped to contain the devastation in least developed and developing countries. The reality is that the pandemic is still ongoing, and the Global South led by South Africa and India are seeking a waiver of provisions to the TRIPS Agreement to ensure that COVID-19 therapeutics, diagnostics, and vaccines reach their citizens in order to contain the spread of the COVID-19 virus ("the TRIPS waiver"). These citizens are especially vulnerable because of their inability to access vaccines due to their prices and supply shortages caused by the refusal to share manufacturing technology. The Doha Declaration aimed at reaffirming the interpretation and implementation of the TRIPS Agreement to support WTO members' right to protect public health and promote access to medicines. However, the operationalization of the Declaration via Article 31bis of TRIPS has been cumbersome and procedurally difficult to navigate. This paper argues that the current iteration of the Doha Declaration within TRIPS fails to meet the objectives of the Declaration as demonstrated by the need for a further waiver of the TRIPS agreement. It also attempts to "reimagine" Article 31 bis in light of the TRIPS waiver from the position of the Global South to make it more equitable and practicable and maintain the spirit of the Declaration.
Keywords: 300; Access to Medicines; Article 31bis; COVID-19; Diagnostics; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Free Trade Agreements (FTAs); Intellectual Property; Kenya; Pandemic; Paragraph 6; Public Health; Therapeutics; TRIPS; TRIPS Agreement; TRIPS Flexibilities; TRIPS Plus; TRIPS Waiver; United States-Kenya Free Trade Agreement (USKEFTA); Vaccines